PROFESSIONAL EXAMINATIONS. - Chamberlain, Heny T. (The Accounting Review, 1942)
Abstract This article presents the questions and answers to the problems which were presented as the first half of the May 1942, Certified Professional Accountant examination in accounting theory in the U.S. The first problem stated that the Elgin Supply Company had acquired previously (December 31, 1939), 90 per cent of the $200,000 common stock of the Peoria Phonograph Company for $126,000. The candidates were required to prepare consolidated balance sheet of December 31, 1941. and statement of minority interests as well as statement of consolidation surplus and goodwill. The second problem started by stating that Morton and Norton were retail dry goods merchants and operated a cash store, with no credit being extended to customers. The business was conducted as a partnership in which Morton had a two-thirds and Norton a one-third interest (capital as well as profits). The candidates were asked to prepare a columnar worksheet, dearly showing the adjustment of the trial balance in accordance with the data given, the operating results in the month of January as distinct from the fire loss, the amount of the fire loss, and the final liquidation of assets and liabilities other than cash, thus leaving on the books only the cash and the two capital accounts.